Immunoassay of chemical contaminants in milk: A review - Fei XU; Kang REN; Yu-ze YANG; Jiang-peng GUO; Guang-peng MA; Yi-ming LIU; Yong-qiang LU; Xiu-bo LI (Journal of Integrative Agriculture, 2015)
The detection of chemical contaminants is critical to ensure dairy safety. These contaminants include veterinary medicines, antibiotics, pesticides, heavy metals, mycotoxins, and persistent organic pollutants (POPs). Immunoassays have recently been used to detect contaminants in milk because of their simple operation, high speed, and low cost. This article describes the latest developments in the most important component of immunoassays — antibodies, and then reviews the four major substrates used for immunoassays (i.e., microplates, membranes, gels, and chips) as well as their use in the detection of milk contaminants. The paper concludes with prospects for further applications of these immunoassays.